PHASE TRANSITION AND MIXING BEHAVIOUR OF THE CUMMINGTONITE-GRUNERITE SOLID SOLUTION - Boffa Ballaran T.; Carpenter M.A.; Domeneghetti M.C. (My University, 2001)
Natural amphiboles with composition close to the binary join cummingtonite-grunerite and crystals of the same samples annealed at 700 °C for 55.5 h, in order to obtain different degrees of non-convergent cation order, have been characterised by means of X-ray single-crystal diffraction and IR spectroscopy. Long-range order parameters describing the non-convergent order of Mg/Fe among the different octahedral sites have been calculated from the site occupancies of the investigated samples. Values of the O6-O5-O6 angles and of the mean bond distances depend on the C2/m → P215>m phase transition for a given degree of order. In the IR spectra, only two phonon lines dominated by the bending of the tetrahedral chains are sensitive to the displacive phase transition and to the different degree of cation order; all the other wavenumber shifts are correlated with compositional changes only. The local strains arising from the cation substitution, ordering and phase transition have been quantified by means of the autocorrelation function. Very small local heterogeneities are associated with the Mg/Fe substitution and disordering in samples at intermediate composition. The displacive phase transition seems to occur in order to reduce local distortions and the P215>m samples are as homogeneous as orthorhombic anthophyllites. The orthorhombic structure, however, appears less flexible than the monoclinic in accommodating cations larger than Mg at the octahedral sites.
Keywords: CUMMINGTONITE; SOLID SOLUTION; CATION ORDERING; PHASE TRANSITION; IR SPECTROSCOPY